Reusability technology in developing expert module for its using QPT approach / Rohani Abu Bakar - Rohani , Abu Bakar (2004)
Intelligent Tutoring System (ITS) has becomes an important teaching aid especially in self-learning environment. Many ITS that have been built have similar architecture but contains different expert module. Traditionally, the expert module was constructed in every ITS development even through the knowledge representation is reusable. In order to reduce the reconstruction cost, we study the possibility of making the knowledge representation reusable by building software that allows the compromise of the expert knowledge to be created and reused. Qualitative Process Technique has been used as the knowledge representation for modeling different subject domains. Two different science subjects; chemistry and physics have been chosen as models to test the effectiveness using a prototype that will be developed in this study to generate an expert module. The knowledge which is modeled is shown using a narrative text that explains the graphical representation of the subject domain.